Factores psicosociales en el inicio de la vida sexual y reproductiva en los estudiantes de bachillerato de la unidad educativa “Ricaurte” del cantón Urdaneta de la provincia de los Ríos - Vera Zapata, Juan Antonio (2016)
Sexuality is a subject little addressed in the social systems in which an individual interacts, because it is labeled "not very pleasant" for many and even considered taboo; The lack of information allows the creation of prejudices in different aspects of sexuality. Adolescence is a stage where the individual experiences a boom (explosion / abundance, etc.) of emotions. IT is a period of great importance in the development of the human being. During this process there are biological, psychological, social, and sexual changes where the adolescent discovers his own identity and their individual autonomy. It should be noted that at this stage most adolescents begin to be sexually active. In this research we can find that several factors influence this activity to occur at younger ages. Parental-filial communication, group pressure, and unreliable information sources are among the main factors that influence the decision-making process of adolescents. It is therefore essential to have an education on sexuality that allows a responsible life in all steps of human development.